2016
DOI: 10.1155/2016/2952635
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Analogue-Related Proximal Renal Tubular Dysfunction during Long-Term Treatment of Chronic Hepatitis B: A Cross-Sectional Study

Abstract: Background. There have been few reports of nucleotide analogue-related renal tubular dysfunction (RTD) in CHB patients. We assessed the prevalence and presentation of nucleotide analogue-related proximal RTD. Methods. A cross-sectional study was performed in CHB patients taking nucleotide analogues. Inclusion criteria were patients who were on adefovir or tenofovir as mono- or add-on therapy with lamivudine (LAM) >1 year. Serum and urine were collected. Fractional excretion of phosphate (FEPO4), uric acid (FEU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…A recent meta-analysis study revealed no significant differences between ETV and TDF treatment in CHB patients in terms of renal safety profiles and hypophosphatemia; however, the short duration of the study limited the power of the conclusions [4][5][6]17]. In contrast to these studies [4][5][6]17], PRTD and impaired phosphate renal tubular reabsorption were seen in 15-48% of CHB patients receiving long-term ADV and TDF therapy as in real world clinical experience [8,10,[18][19][20]. Reversibility of renal dysfunction has been shown in HIV-infected patients after cessation of TDF [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…A recent meta-analysis study revealed no significant differences between ETV and TDF treatment in CHB patients in terms of renal safety profiles and hypophosphatemia; however, the short duration of the study limited the power of the conclusions [4][5][6]17]. In contrast to these studies [4][5][6]17], PRTD and impaired phosphate renal tubular reabsorption were seen in 15-48% of CHB patients receiving long-term ADV and TDF therapy as in real world clinical experience [8,10,[18][19][20]. Reversibility of renal dysfunction has been shown in HIV-infected patients after cessation of TDF [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 90%
“…Written inform consent was obtained from the study subjects before recruitment. Out of 92 CHB patients who had been treated with nucleotide analogue, 24 patients were found to have nucleotide analoguerelated PRTD from our previous study [20]. Renal loss of protein, glucose, phosphate, uric acid, potassium, and bicarbonate was defined via laboratory assays.…”
Section: Study Design and Patient Populationmentioning
confidence: 99%
See 3 more Smart Citations